"Our Little Patients": A Case Study of Hospitalized Children at the University of Michigan, 1890–2011. (July 2013) - Hirshbein, Laura
Perceptions of hospitalization for children shifted from late nineteenth-century care designed to uplift poor children and create better citizens to mid-century attention to children's emotional and medical needs. In the last few decades, sick children have become objects of sympathy and outpourings of affection. The history of hospitalized children at the University of Michigan demonstrates change over time in involvement of caregivers and families, the role of education during sickness, and the value placed on illness. The hospital provided more than just medical interventions, and its history offers a window to changing ideas about children and society.